Implicit Methods for Studying Attitudes: Modern Approach to Research in Social Sciences - Plotka, Irina; Blumenau, Nina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of paper is to analyze the experience of the experimental studying of attitudes by implicit methods in social sciences. It is an experience of collaborative research of graduates and professors to develop a new tool - experimental procedures of the implicit association test and unconscious priming to measure various psychological constructs.The involvement of students into the creative atmosphere underpins the formation of a creative, competent and responsible psychologist who could learn how to work in any field of psychology. The concisely presented results of empirical research are focused on the study of ethnic attitudes, hardiness, gambling addiction and addiction to alcohol with implicit methods and self-assessment procedures. On the example of gambling addiction considered in detail,the benefits of implicit measurements were revealed. Implicit methods are successfully used not only in social psychology and its applied fields, but also in pedagogy (in revealing creative abilities).